(untitled) (Indian Journal of Forensic Medicine & Toxicology, 2020)
Background: Menopausal women shows common symptoms which includes night sweats and hot flushes,heart distress, disturbances in sleep, depression, irritability, anxiousness, weight changes, physical andmental fatigue, joint and muscle pain. This affects the Quality Of Life of the Menopausal women. PilatesTraining has proven beneficial for enhancing Quality Of Life in menopausal women but there is paucityof evidence of effect of Progressive Muscle Relaxation Technique in Menopausal women on QOL. Theresearch is an initiative study that focuses on the effectiveness of PMRT on the various aspects of QualityOf Life of the menopausal women and comparison of the Pilates training and PMRT in order to enhance theQOL of participants.Aim and Objective: Effect of Pilates training & Progressive Muscle Relaxation Technique on menopausalwomen’s Quality Of Life and comparison of both the technique.Methods: 42 participants aged more than 45 years will be randomly categorized in two groups: Group A(n= 21) and Group B (n=21). The study duration will be of 6 months. The pre and post Intervention willbe taken from both the group and data will be analyzed with the help of main outcome measure which isMenopause specific Quality Of Life (MENQOL).Result- The expected result would include the details about whether the measures are effective for improvingthe quality of life in menopausal women, as well as the comparison of both the interventions. Data will beanalyzed using paired t-test.Conclusion- It will be published after results are analyzed